2010
DOI: 10.1128/mcb.00917-10
|View full text |Cite
|
Sign up to set email alerts
|

Dual Functions of Nbs1 in the Repair of DNA Breaks and Proliferation Ensure Proper V(D)J Recombination and T-Cell Development

Abstract: DNA double-strand breaks (DSBs) are generated by exogenous DNA damage stimuli (e.g., ionizing radiation) and endogenous metabolic intermediates, such as collapsed replication forks. Upon DSB generation, NBS1 together with MRE11 and RAD50 form the MRN complex (26). MRE11, which contains two DNA binding domains, mediates the MRN complex binding to the exposed DNA ends. The adjacent MRNassociated DNA ends could be further tethered together through the coiled-coil domain (zinc hook) of RAD50 (19,43). The chromatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 49 publications
(67 reference statements)
4
30
2
Order By: Relevance
“…This result is the further extension of the ability of NBS1 to interact with both the upstream PI3K and downstream Akt to regulate the activity of PI3K/Akt pathway. It is also supported by recent literatures demonstrating the dual function of NBS1 in the repair of DNA breaks and proliferation and the requirement of NBS1 in IGF-1 induced cellular proliferation [25], [26]. In addition, the ability of RNA regulon to promote Akt activity also goes through the upregulation of NBS1 levels [27].…”
Section: Discussionsupporting
confidence: 72%
“…This result is the further extension of the ability of NBS1 to interact with both the upstream PI3K and downstream Akt to regulate the activity of PI3K/Akt pathway. It is also supported by recent literatures demonstrating the dual function of NBS1 in the repair of DNA breaks and proliferation and the requirement of NBS1 in IGF-1 induced cellular proliferation [25], [26]. In addition, the ability of RNA regulon to promote Akt activity also goes through the upregulation of NBS1 levels [27].…”
Section: Discussionsupporting
confidence: 72%
“…In murine models, loss of NBS1 hinders T‐cell development at an early developmental stage 60. Mechanistically, NBS1 depletion compromises loading of the MRN complex to V(D)J‐generated DSBs and thereby affects DNA end resection 60…”
Section: Genes and Diseases Associated With Defective Recombination Imentioning
confidence: 99%
“…Most of the studies concerning the role of the Mre11 complex in these processes rely on effects observed upon deletion of one of its subunits (6) (7). However, it is conceivable that abnormal cell cycle progression, proliferation and increased mortality consequent to Mre11 complex ablation have impeded an appropriate characterization of its influence, as well as its relationship with ATM, in the repair of physiological breaks.…”
Section: Introductionmentioning
confidence: 99%